Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Karyawan - Asyifa Dinda Ramadhanti; Epi Fitriah (UNISBA Press, 2022)
Abstract. Employee performance is a form of an employee's success in achieving the strategic goals that have been set with the expected behavior. One of the factors that can affect employee performance is the implementation of good corporate governance in the company with the principles of transparency, accountability, responsibility, independence, and fairness. The implementation of Good Corporate Governance (GCG) is a form of implementing the company's control and management process that contains policies and regulates the relationships and responsibilities between employees, creditors and stakeholders in order to realize the company's goals. This study aims to determine the application of good corporate governance, employee performance and the effect of the implementation of good corporate governance on employee performance at hospitals in Bandung. The source of data in this research is primary data. The method used is a survey method by distributing questionnaires to 50 hospital employees in Bandung. The sampling technique used by the researcher is non-probability sampling with convenience sampling technique. Statistical testing used is simple regression analysis, hypothesis testing and analysis of the coefficient of determination using SPPS 17. From the results of this study it can be concluded that the implementation of good corporate governance in hospitals in the city of Bandung has the criteria of